Analisis Strategi Pemasaran pada Simpanan Qurban di BMT Alhikmah Permata Cabang Plajan - Nureza Ayu Kumalasari; Miswan Ansori; Ahmad Fauzan Mubarak (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the opportunities and barriers in marketing the Qurban Savings product at BMT Al-Hikmah Permata. This study employs a qualitative approach, with data collection techniques including interviews, observation and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Qurban Savings product has significant market potential, supported by the strong tradition of the Qurban ritual and the high level of public interest in performing it. This product also serves as an alternative solution for those with limited funds through a gradual savings system. However, the marketing of the product still faces several obstacles, such as low public literacy regarding the product, perceptions equating it with conventional savings groups, the habit of performing qurban directly, low savings discipline, unstable economic conditions, as well as competition with other financial institutions and more established qurban savings groups. These findings indicate that marketing success is influenced not only by market potential but also by the level of public understanding and trust. Therefore, strategies are required to enhance education, promote the product based on religious values, innovate the deposit system, and improve service quality so that the product can develop more effectively.